Perancangan Data Warehouse Menggunakan Metode Nine Step Pada PT. XYZ - Shevchenko, Angelus Galang; Maharani, Wianti; Wijaya, Andri (CV. ITTC INDONESIA, 2025)
PT. XYZ operates in the food distribution sector and handles a large number of inbound and outbound goods transactions each day. The high transaction volume creates challengess in managing inventory effectively, highlighting the need for an integrated data management solution. This research aims to develop a data warehouse for PT. XYZ by applying the Kimball Nine-Step methodology. Data were collected through interviews, field observations, and a review of relevant literature. The data warehouse design process includes identifying fact tables and dimension tables related to receiving and shipping activities, followed by the implementation of the Extract, Transform, Load (ETL) process using SQL Server Management Studio 19. The findings indicate that the proposed data warehouse is capable of integrating operational data and presenting inventory information through reports generated using Microsoft Excel. The system supports improved stock control and enables management to make faster and more accurate decisions.